2005
DOI: 10.1051/rnd:2005056
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with safflower seeds differing in fatty acid composition differentially influences serum concentrations of prostaglandin F metabolite in postpartum beef cows

Abstract: -Synthesis and secretion of prostaglandin F 2α (PGF 2α ) is elevated following parturition and exerts divergent effects on the re-establishment of fertile estrous cycles in cows. The objective of these experiments was to determine if oil seed supplements differing in fatty acid composition differentially influence serum concentrations of the specific PGF 2α metabolite, PGFM. Safflower seed supplements were formulated to provide 5% of dry-matter intake as fat. In Trial 1, 24 multiparous beef cows were individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…However, previous reports indicate that linoleic acid can hinder PGF 2α synthesis by competitive inhibition of the enzymes ∆ 6 -desaturase and cyclooxygenase (Staples et al, 1998;Cheng et al, 2001). Still, others have reported that supplementation with linoleic acid sources after breeding increased circulating concentrations of PGF 2α metabolite and reduced pregnancy rates in beef cows (Filley et al, 2000;Grant et al, 2005). Supplementation with linolenic acid, on the other hand, inhibits synthesis of PGF 2α and reduces pregnancy losses in cattle (Pace-Asciak and Wolfe, 1968;Thatcher et al, 1994;Ambrose et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…However, previous reports indicate that linoleic acid can hinder PGF 2α synthesis by competitive inhibition of the enzymes ∆ 6 -desaturase and cyclooxygenase (Staples et al, 1998;Cheng et al, 2001). Still, others have reported that supplementation with linoleic acid sources after breeding increased circulating concentrations of PGF 2α metabolite and reduced pregnancy rates in beef cows (Filley et al, 2000;Grant et al, 2005). Supplementation with linolenic acid, on the other hand, inhibits synthesis of PGF 2α and reduces pregnancy losses in cattle (Pace-Asciak and Wolfe, 1968;Thatcher et al, 1994;Ambrose et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…However, previous research indicated that linoleic acid can reduce PCF2a synthesis by inhibiting the enzymes Ag-desaturase and cyclooxygenase (Staples et al, 1998;Cheng et al, 2001). Nevertheless, research studies demonstrated that .supplementation with linoleic acid to beef cows after breeding increased circulating concentrations of PGF2" metabolite and reduced overall pregnancy rates (Filley et al, 2000;Grant et al, 2005). Conversely, linolenic acid is a precursor of eicosapentaenoic and docosahexaenoic acids, which have been shown to inhibit cyclooxygenase activity and consequently PGF2« synthesis (Yaqoob and Calder, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…No treatment effects were also detected (P ≥ 0.12) for expression of endometrial, luteal, and conceptus genes associated with pregnancy establishment (Table 9). As previously mentioned, ω-6 FA are known to modulate synthesis of PG associated with luteolysis (PGF 2α ; Staples et al, 1998;Cheng et al, 2001;Grant et al, 2005) and pregnancy establishment (PGE 2 and PGI 2 ; Dorniak et al, 2011) via cyclooxygenase-2 activity (Schmitz and Ecker, 2008), whereas PGF 2α simulates luteal oxytocin production (Skarzynski et al, 1997). However, CSSO-supplemented and CON cows had similar mRNA expression of luteal oxytocin and PG receptor (P ≥ 0.12) as well as endometrial cyclooxygenase-2 and oxytocin receptor (P ≥ 0.24) on d 19 after AI (Table 9), despite the greater concentration of ω-6 FA in luteal and endometrial tissues of CSSOsupplemented cows.…”
Section: Expression Of Genes Associated With Pregnancy Establishmentmentioning
confidence: 99%
“…Supplemental PUFA has been shown to alter fatty acid (FA) profile in reproductive tissues of beef cows, including the corpus luteum (CL) and endometrium (Burns et al, 2003;White et al, 2012). Dietary PUFA are also known to modulate hormones associated with pregnancy establishment, such as PG and progesterone (P4; Hawkins et al, 1995;Grant et al, 2005). Based on these findings, we hypothesized that CSSO supplementation during early gestation increases incorporation of PUFA into maternal reproductive tissues and the conceptus.…”
Section: Introductionmentioning
confidence: 99%